Bacillus Calmette–Guérin in Immuno-Regulation of Alzheimer’s Disease - Klein, Benjamin Y.; Greenblatt, Charles L.; Gofrit, Ofer N.; Bercovier, Hervé (Frontiers in Aging Neuroscience, 2022)
Bacillus Calmette–Guérin is frequently the treatment of choice of superficial bladder cancer. Exposing the urinary bladder of elderly patients with bladder cancer to the BCG vaccine reduced the risk of Alzheimer’s disease (AD) substantially. Vaccines against other infectious microorganisms by other vaccination methods showed a similar but a lesser effect. This suggests that immune effects on AD are antigenically non-specific, likely being a metabolic result of immune system activation, similar to that shown for Juvenile diabetes. In this mini review we point to the benefit of BCG vaccine. We then briefly highlight the pathological involvement of the immune system in the AD both, in the peripheral and the central (brain) compartments. Given the uncertain prophylactic mechanism of the BCG effect against AD we propose to take advantage of the therapeutically planned bladder exposure to BCG. Based on pathological aggregation of wrongly cleaved amyloid precursor protein (APP) resistant to the unfolded protein response (UPR) which results in amyloid beta plaques we predict that BCG may impact the UPR signaling cascade. In addition pathways of innate immunity training concerned with energy metabolism, predict capability of activated immune cells to substitute deranged astrocytes that fail to support neuronal energy metabolism. This mini review points to ways through which immune cells can mediate between BCG vaccination and AD to support the wellness of the central nervous system.